Friendship stability in adolescence is associated with ventral striatum responses to vicarious rewards - Elisabeth Schreuders (Nature Portfolio, 2021)
A reward-related ventral striatum response is observed when rewards are gained for friends. Here the authors examine how this response changes from childhood to young adulthood, and show that friendship stability in adolescence is associated with ventral striatum responses to vicarious rewards.